Colorectal polypoid lesions and expression of vascular endothelial growth factor in a consecutive series of endoscopic and surgical patients. Issue 3 (March 2017) - Ruffolo, Cesare; Toffolatti, Luisa; Canal, Fabio; Kotsafti, Andromachi; Pagura, Giulia; Pozza, Anna; Campo Dell'Orto, Marta; Ferrara, Francesco; Massani, Marco; Dei Tos, Angelo P; Castoro, Carlo; Bassi, Nicolò; et al.
Colorectal cancer incidence in patients undergoing screening protocols is decreasing because of the higher rate of discovered preneoplastic colonic lesions; however, adenomatous polyps may not always be removable endoscopically and surgery may still be necessary. The aim of this study was to assess the vascular endothelial growth factor expression in the different steps of colorectal carcinogenesis to explore its potential role as a marker of malignancy in polypoid lesions. A total of 92 subjects with colonic adenoma or cancer who underwent screening colonoscopy or surgery were prospectively enrolled. Real-time reverse transcription polymerase chain reaction for VEGF-A messenger RNA expression and immunohistochemistry for VEGF-A were performed. Immunoassays for VEGF-A, VEGF-C, VEGFR-1, VEGFR-2, and VEGFR-3 were also performed. Non-parametric statistics, receiver operating characteristic curve analysis, and logistic multiple regression analysis were used. VEGF-A messenger RNA expression was higher in patients with high-grade dysplasia or colorectal cancer than in those with low-grade dysplasia adenomas (p = 0.01). At immunohistochemistry, VEGF-A expression was significantly higher in colorectal cancer patients compared to dysplastic adenomas (p < 0.001), and the accuracy of VEGF-A expression for prediction of malignancy was 91.7 (95% confidence interval = 78.7–97.9). VEGF-C protein expression was lower in colorectal cancer patients than in simple adenomas (p = 0.02). VEGF-A levels were directly correlated to polyp size (rho = 0.73, p = 0.0062). Multivariate analysis demonstrated that malignancy and polyp size were independent predictors of VEGF-A mucosal levels. This study demonstrated that the VEGF-A expression changes along the colorectal carcinogenesis pathway showing a neat step up at the passage from high-grade dysplasia to invasive cancer. This feature might potentially be useful to stratify colorectal polyps in different risks of progression classes. Moreover, the high level of VEGF-A expression predicted the presence of lymphovascular invasion with good accuracy.